Novel Fabrication and Enhanced Photocatalytic MB Degradation of Hierarchical Porous Monoliths of MoO3 Nanoplates - Yang Liu (Nature Portfolio, 2017)
Abstract Porous monoliths of MoO3 nanoplates were synthesized from ammonium molybdate (AHM) by freeze-casting and subsequent thermal treatment from 300 to 600 °C. Pure orthorhombic MoO3 phase was obtained at thermal treatment temperature of 400 °C and above. MoO3 monoliths thermally treated at 400 °C displayed bimodal pore structure, including large pore channels replicating the ice crystals and small pores from MoO3 sheets stacking. Transmission electron microscopy (TEM) images revealed that the average thicknesses of MoO3 sheet were 50 and 300 nm in porous monoliths thermally treated at 400 °C. The photocatalytic performance of MoO3 was evaluated through degradation of methylene blue (MB) under visible light radiation and MoO3 synthesized at 400 °C exhibited strong adsorption performance and best photocatalytic activity for photodegradation of MB of 99.7% under visible illumination for 60 min. MoO3 photocatalyst displayed promising cyclic performance, and the decolorization efficiency of MB solution was 98.1% after four cycles.